Pelatihan konselor sebaya bagi mahasiswa Kampus V PGSD Pare-Pare - Musfirah Musfirah; St. Maryam M; Hamzah Pagarra (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The Community Partnership Program (PKM) partner is PGSD kampus V Parepare. Problems often experienced by students such as lack of motivation, dropping out of college, hedonism, procrastination, juvenile delinquency, drug use, promiscuity and other problems. Facts on the ground in early 2019, there were students who committed suicide on campus V UNM Parepare. These problems if not resolved as soon as possible can disrupt the psychological development of students, so it needs a solution in solving them. 'Due to the above problems, it is considered necessary to do peer counselor training for PGSD kampus V Parepare students so that they can help each other if friends experience problems. If students are able to help their peers, they will reduce their burden in facing the problems they are facing so that students can develop optimally without the pressure of problems. Training objectives: 1) Provide an explanation to students about the basic concepts of peer counselors; 2) Providing skills to students about peer counselor techniques 3) Developing and practicing peer counselor techniques for students. Benefits: 1) the benefits that can be obtained are generally students are able to know the advantages and disadvantages of each peer counseling techniques that have been implemented. the methods used in this training are lecture, demonstration, and practice methods. As for the material given is divided into: 1. Presentation of Material. 2. Practice. The implementation of peer counselor training activities has been successful based on a percentage of 85% and an outcome of 90%. The response of participants to the implementation of peer counselor training activities was very good, as seen from the indicator of student attendance which reached 90%. Besides that, during the activity, the students were very enthusiastic in following the activity from the beginning to the end.